2023
DOI: 10.3390/ani13142323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Faecal Microbiota Composition Following a Dairy By-Product Supplemented Diet in Nero Siciliano and Large White × Landrace Pig Breeds

Abstract: The current study compared the faecal microbiota composition of two pig breeds (autochthonous vs. commercial) to understand what happens after the integration of liquid whey in the diet and what the role of the host genetic is. The trial was conducted for 60 days, and the faecal microbiota composition was investigated at three time points, T0, T1 (after 30 days) and T2 (after 60 days) in 30 female pigs (20 commercial crossbred and 10 Nero Siciliano pigs). The animals were divided into four groups (two control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Genomic sequences of domestic and wild pigs have been observed to be predominantly similar, except in regions under strong selection pressure [10]. Various authors have reported on selection in domestic pigs for disease resistance, tolerance, and productivity [37][38][39]. Information on selection signatures is valuable and can be used in management strategies to improve production and adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic sequences of domestic and wild pigs have been observed to be predominantly similar, except in regions under strong selection pressure [10]. Various authors have reported on selection in domestic pigs for disease resistance, tolerance, and productivity [37][38][39]. Information on selection signatures is valuable and can be used in management strategies to improve production and adaptability.…”
Section: Introductionmentioning
confidence: 99%